Healthcare Workers' Attitudes Toward Patients With Ebola Virus Disease in The United States. (9th December 2015) - Narasimhulu, Deepa Maheswari; Edwards, Vernee; Chazotte, Cynthia; Bhatt, Devika; Weedon, Jeremy; Minkoff, Howard
Abstract : Healthcare worker's willingness to care for Ebola patients did not precisely mirror their beliefs about the ethics of refusing to provide care, they were strongly influenced by concerns about potentially exposing families and friends to Ebola virus disease. Abstract: Background. We assessed healthcare workers' (HCWs) attitudes toward care of patients with Ebola virus disease (EVD). Methods. We provided a self-administered questionnaire-based cross-sectional study of HCWs at 2 urban hospitals. Results. Of 428 HCWs surveyed, 25.1% believed it was ethical to refuse care to patients with EVD; 25.9% were unwilling to provide care to them. In a multivariate analysis, female gender (32.9% vs 11.9%; odds ratio [OR], 3.2; 95% confidence interval [CI], 1.4–7.7), nursing profession (43.6% vs 12.8%; OR, 2.7; 95% CI, 1.4–5.2), ethical beliefs about refusing care to patients with EVD (39.1% vs 21.3%; OR, 3.71; 95% CI, 2.0–7.0), and increased concern about putting family, friends, and coworkers at risk (28.2% vs 0%; P = .003; OR, 11.1) were independent predictors of unwillingness to care for patients with EVD. Although beliefs about the ethics of refusing care were independently associated with willingness to care for patients with EVD, 21.3% of those who thought it was unethical to refuse care would be unwilling to care for patients with EVD. Healthcare workers in our study had concerns about potentially exposing their families and friends to EVD (90%), which was out of proportion to their degree of concern for personal risk (16.8%). Conclusion. Healthcare workers' willingness to care for patients with Ebola patients did not precisely mirror their beliefs about the ethics of refusing to provide care, although they were strongly influenced by those beliefs. Healthcare workers may be balancing ethical beliefs about patient care with beliefs about risks entailed in rendering care and consequent risks to their families. Providing a safe work environment and measures to reduce risks to family, perhaps by arranging child care or providing temporary quarters, may help alleviate HCW's concerns.